Effect of direct aging heat treatment on microstructures and properties of CuCrZr alloy manufactured by laser powder bed fusion - Runze Zhang; Junyan Fang; Yongming Guo; Huaixue Li; Lei Shi; Peng Liu (Journal of Materials Research and Technology)
Effect of heat treatment on the microstructures and properties of CuCrZr alloy fabricated by laser powder bed fusion (LPBF) were investigated using OM, SEM, EBSD, TEM and electrochemical tests. However, due to the significant non-equilibrium solidification process during LPBF, residual stress and microstructural inhomogeneity are prone to occur in the alloy. This paper employed a direct aging heat treatment (DAHT) process (475 °C+90min) to induce recrystallization and precipitation of strengthening phases, thereby improving the properties of alloys. The results showed that the grain size of the alloy was significantly reduced, with the XOY plane being 49.8um and the XOZ plane being 96.5um. The proportion of high-angle grain boundaries (HAGBs) also increased significantly, with the HAGB proportions in the XOY and XOZ planes being 76.3 % and 76.5 %, respectively. The dislocation density and strain level of the alloy were also reduced, with the KAM values of the XOY and XOZ planes both dropping to 0.32, and the dislocation densities decreasing to 2.19 × 1013 m−2 and 2.11 × 1013 m−2, respectively. Meanwhile, a large number of nano-scale Cr-rich precipitates were present at the grain boundaries and within the grains. The hardness of the alloy increased by about 75 %, and its corrosion resistance was also significantly enhanced, with the highest corrosion potential being −128.6 mV and the lowest corrosion current density being 1.40 × 10−5A/cm2. Therefore, the DAHT process can enhance the properties of LPBF-fabricated CuCrZr alloy, providing an important research basis for the preparation of high-performance copper alloys using LPBF technology and their wider application.